Euconnus malakkanus Franz transferred to Elacatophora Schaufuss (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
The female holotype of Euconnus malakkanus Franz is recognized as belonging in Elacatophora Schaufuss; the species is transferred resulting in Elacatophora malakkana (Franz), comb. n. Although known only from a female, this species seems to be different from its morphologically uniform congeners, as demonstrated by comparing measurements and proportions of body parts. A checklist of all currently known species of Elacatophora with complete synonymy and distribution is provided.